Pengaruh Struktur Modal, Likuiditas Dan Efisiensi Operasional Terhadap Kinerja Keuangan Pada PT Surya Citra Media Tbk Periode 2014-2024 - Sevty Karina Indika; Hengki Hermawan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of capital structure, liquidity, and operational efficiency on the financial performance of PT Surya Citra Media Tbk during the period 2014–2024. The independent variables used in this study are the debt to equity ratio, current ratio, and total asset turnover, while the dependent variable is return on assets. This research employs a quantitative approach with a causal associative method to describe data patterns and measure the relationships among variables. The data used are secondary data obtained from company documents and financial statements. The statistical analysis includes classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The results show that partially the debt to equity ratio has a significant effect on financial performance with Tcount 2.737 > Ttable 2.021 and significance 0.029 < 0.05. The current ratio partially has a significant effect on financial performance with Tcount 2.782 > Ttable 2.021 and significance 0.027 < 0.05. The total asset turnover partially has a significant effect on financial performance with Tcount 8.706 > Ttable 2.021 and significance <0.001 < 0.05. Based on the F-test, the debt to equity ratio, current ratio, and total asset turnover simultaneously have a significant effect on the financial performance of PT Surya Citra Media Tbk with Fcount 25.747 > Ftable 2.839 and significance <0.001 < 0.05.